PENERAPAN AJARAN TRI PARARTHA DALAM MENINGKATKAN PENGUATAN PENDIDIKAN KARAKTER SISWA KELAS VII DI SMP NEGERI 1 BANGLI - Julistyawan, I Komang; Karsana, I Nengah; Arimbawa, I Nengah (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2023)
Character education is an important aspect in the formation of a good personality, especially for students at SMP Negeri 1 Bangli. thus, one of the teachings that are used in increasing the strengthening of character education in students is the Tri Parartha teaching. Tri Parartha is the three concepts of happiness, namely compassion, gift add a comma devotion. These three concepts will help students strengthen their character education in students.The formulation of the problems discussed in this study are as follows: (1) How is the application of the teachings of Tri Parartha in enhancing the strengthening of character education for class VII students at SMP Negeri 1 Bangli? (2) What are the obstacles and efforts made in implementing Tri Parartha's teachings in increasing the strengthening of character education for class VII students at SMP Negeri 1 Bangli? (3) What are the implications of applying the teachings of Tri Parartha in increasing the strengthening of character education for class VII students at SMP Negeri 1 Bangli?The results obtained in this study are: (1) the form of application of Tri Parartha's teachings, namely the application of compassion, for example caring for others and caring for the environment, punia, namely by sharing, for example, and the form of applying devotional service, for example saying greetings and greetings, and praying together. (2) the obstacles in applying the teachings of Tri Parartha come from two factors, namely internal (internal) and external (external) factors. Efforts are being made to overcome these obstacles by increasing the role of teachers and increasing the role of parents. (3) the implications that arise in the application of the Tri Paratha teachings, namely: implications for religious character, nationalist character, cooperation character, integrity character, and independent character. Keywords: Teachings of Tri Parartha, strengthening student character education